2022
DOI: 10.1177/00027642211066039
|View full text |Cite
|
Sign up to set email alerts
|

Trucking in the Era of COVID-19

Abstract: COVID-19 resulted in health and logistical challenges for many sectors of the American economy, including the trucking industry. This study examined how the pandemic impacted the trucking industry, focused on the pandemic’s impacts on company operations, health, and stress of trucking industry employees. Data were collected from three sources: surveys, focus groups, and social media posts. Individuals at multiple organizational levels of trucking companies (i.e., supervisors, upper-level management, and driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…No less than 96% of LSPs have problems finding drivers for road transport. The results are somewhat expected, as the studies by Brooks et al [42] and Sperry et al [43] also highlight the problems faced by road transport companies during the pandemic. Only 4% of the companies reported staffing problems in maritime and rail transport.…”
Section: Resultssupporting
confidence: 59%
“…No less than 96% of LSPs have problems finding drivers for road transport. The results are somewhat expected, as the studies by Brooks et al [42] and Sperry et al [43] also highlight the problems faced by road transport companies during the pandemic. Only 4% of the companies reported staffing problems in maritime and rail transport.…”
Section: Resultssupporting
confidence: 59%
“…One is that the questionnaire was conducted at the end of 2021. During the COVID-19 pandemic, truck drivers dealt with less social contact as amenities closed down, while social media sentiment analysis revealed that public appreciation for their work actually grew ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this are also similar to those of other sectors, such as supply chain disruptions, demand declines, and restrictive government policies in response to the pandemic. A lack of adequate government supports make trucking companies quite vulnerable to the health and economic risks of COVID-19 ( Sperry et al, 2022 ). Following the vaccine discovery announcement date, stock prices in the trucking sector reacted with slightly positive returns.…”
Section: Discussionmentioning
confidence: 99%